Computer numerical control (CNC) /c Habeeb Alani, Kumaran Kadirgama, Rosli Abu Bakar - Habeeb Alani; Kumaran Kadirgama; Rosli Abu Bakar (Penerbit Universiti Malaysia Pahang, 2012)
This book will give the CNC user several side benefits, including reduced operator fatigue